2013
DOI: 10.1016/j.ijcard.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Associations between DSM-IV mental disorders and subsequent heart disease onset: Beyond depression

Abstract: Background Prior studies on the depression-heart disease association have not usually used diagnostic measures of depression, nor taken other mental disorders into consideration. As a result, it is not clear whether the association between depression and heart disease onset reflects a specific association, or the comorbidity between depression and other mental disorders. Additionally, the relative magnitude of associations of a range of mental disorders with heart disease onset is unknown. Methods Face-to-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 42 publications
5
36
2
3
Order By: Relevance
“…It is only by using survival analysis that we are able to exclude such episodes from the predictor set because the data are organised in person-year files. Comparable with previous studies using these data [26, 27], we used discrete-time survival analyses [28] with person-year as the unit of analysis to test associations between first onset of mental disorders and diabetes diagnosis. For these analyses, a person-year dataset was created in which each year in the life of each respondent up to and including the age of onset of diabetes or their age at interview (whichever came first) was treated as a separate observational record, with the year of diabetes onset coded 1 and earlier years coded 0 on a dichotomous outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…It is only by using survival analysis that we are able to exclude such episodes from the predictor set because the data are organised in person-year files. Comparable with previous studies using these data [26, 27], we used discrete-time survival analyses [28] with person-year as the unit of analysis to test associations between first onset of mental disorders and diabetes diagnosis. For these analyses, a person-year dataset was created in which each year in the life of each respondent up to and including the age of onset of diabetes or their age at interview (whichever came first) was treated as a separate observational record, with the year of diabetes onset coded 1 and earlier years coded 0 on a dichotomous outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the associations between mental disorder and COPD diagnosis by using this time-related information. Comparable with previous studies [16,17] using these data we used discrete-time survival analyses [19,20] with person-year as the unit of analysis to investigate sequential associations between first onset of mental disorders and the subsequent diagnosis of COPD. For these analyses a person-year data set was created in which each year in the life of each respondent up to and including the age of diagnosis of COPD or their age at interview (whichever came first) was treated as a separate observational record, with the year of COPD diagnosis coded 1 and earlier years coded 0 on a dichotomous outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…depressive and anxiety disorders. It has a significant impact on compliance with treatment requirements and quality of life with the disease [6]. Research conducted over the years confirmed the impact of psychological factors (such as locus of control, the level of perceived stress, and important life events) as well as psychopathological factors (such as depressive episodes, dysthymia, bipolar disorder, generalized anxiety disorder, and alcohol abuse) on development of cardiovascular diseases and their impact on the prognosis of patients [7].…”
Section: Psychological Aspects Of Cardiac Diseasesmentioning
confidence: 98%